PostNegritude visual and literary culture - Reid, Mark (Mark A.) (SUNY series, cultural studies in cinema/video., 1997)
In the 1960s and 1970s, the civil rights movement and other national and cultural movements fractured dominant paradigms of American identity and demanded a reformulation of American values and norms. This book borrows the moral, ethical, and political purposes of these movements to show how film, literature, photography, and television news broadcasts construct essentialist myths about race, gender, sexuality, and nation. It also examines how some visual and literary works and public reactions challenge these essentialist myths by exploring racial, sexual, and national anxieties.